2019
DOI: 10.1155/2019/3257892
|View full text |Cite
|
Sign up to set email alerts
|

Facile Interpretation of Catalytic Reaction between Organic Dye Pollutants and Silver Nanoparticles with Different Shapes

Abstract: In this study, various shapes of silver nanoparticles (Ag NPs) were synthesized via simple methods in aqueous solution. The size and shape of Ag NPs were measured by TEM image and DLS, and the crystalline form of Ag NPs was confirmed by XRD. From ATR-IR and zeta potential, the Ag NPs were found to be well surrounded by PVP. In addition, the catalytic activity of Ag NPs was evaluated using model dyes. Unlike the conventional catalysts, the model dyes with absorption peaks that did not overlap with the SPR peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This could indicate that the Ag-NPs prepared during the first reduction process (PDI − anion) not only are of smaller size (diameter) than those prepared at potentials exceeding the second reduction process potential but also differ in shape. In addition to Ag-NP spheres, Ag-NPs of other shapes, such as discs, hexagons, or triangles, could be formed [ 43 , 44 ]. Difference spectra (the differences in the absorbance (A) of the hybrid A HL and pristine A PL layers: A dif = A HL − A PL ), which demonstrate improvement in light absorption due to the plasmonic effects of Ag NPs, are shown by green curves in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could indicate that the Ag-NPs prepared during the first reduction process (PDI − anion) not only are of smaller size (diameter) than those prepared at potentials exceeding the second reduction process potential but also differ in shape. In addition to Ag-NP spheres, Ag-NPs of other shapes, such as discs, hexagons, or triangles, could be formed [ 43 , 44 ]. Difference spectra (the differences in the absorbance (A) of the hybrid A HL and pristine A PL layers: A dif = A HL − A PL ), which demonstrate improvement in light absorption due to the plasmonic effects of Ag NPs, are shown by green curves in Figure 2 and Figure 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The maxima of the HL1 difference spectra at 431 and 425 nm for CFC8-DDPDI and CFC8-EHPDI , respectively, correspond well to the SP absorption of spherical Ag-NPs. The red-shifted maxima and long absorption tails in the spectra of the HL2 layers prepared during the second reduction process indicate that Ag-NPs of mixed shapes with red-shifted SP absorption are present in the HL2 layers, such as nanocircular discs with SP absorption at 510–581 nm or hexagonal and truncated nanotriangles with SP at wavelengths >581 nm [ 43 , 44 ]. The SP absorption peak can shift to a higher wavelength with increased aggregation of nanoparticles [ 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…While Balakarthikeyan et al confirmed the nano size between 68 to 100 nm obtained from synthesis using NaBH4 [135]. Ag-NPs synthesized chemically using PVP as stabilizer reported NCs of 20.4 nm in size [136]. Green synthesis utilizing Citrullus lanatus fruit rind as a reductant and capping agent yields stable, spherical Ag-NPs with an average diameter of 17.96 ± 0.16 nm [110].…”
Section: Effected Of Ag Ions Concentration To the Controlling Size Of Ag-npsmentioning
confidence: 97%
“…In addition to attractive morphology, their twin planes are combined with multiple stacking faults [67], causing high reactivity of those planes, resulting in high catalytic activity [68]. In practice it is difficult to determine the catalytic activity of colored AgNP colloids in batch reactors, because their UV-Vis absorbance spectrum can overlap with that of model dyes such as 4-nitrophenol (4-NP), which are commonly converted to study the catalytic activity of metal nanoparticles, including nanoplates [69,70].…”
Section: Introductionmentioning
confidence: 99%